Characteristics and circulation of archipelagic waters with the three-dimensional hydrodynamic model approach - Suhaemi .; D.G. Bengen; C.P.H. Simanjuntak; A.F. Koropitan (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: The Misool Islands are lined up regularly from west to east, the southern part of Raja Ampat Archipelago, Papua - Indonesia. The geomorphology is distinctive, and the coral reef substrate causes turbulence. Misool waters are located in the Papuan bird's head seascape, passed by Pacific water masses. The assessment status of Misool waters as a conservation area does not include hydrodynamic aspects in the decision processes. The present study is fundamental for determining and changing essential areas for conservation. The main objective of this study is to the pattern of hydrodynamic processes and investigate the features of the water mass in the Misool waters.METHODS: An acoustic doppler current profiler was deployed to measure currents every 15 minutes for ten water column layers. Investigation of waters characteristics was using Conductivity-Temperature-Depth equipment. A three-dimensional computational model was performed using MIKE3.FINDINGS: The water mass around the Misool Islands are more influenced by the local oceanographic processes than the water masses from the Pacific Ocean. The study site is characterized by the mixed tide, prevalence to semi-diurnal based on observational tidal data. Wind and baroclinic properties generate non-significant currents, resulting in low horizontal and vertical stratification. Intensification of tidal currents occurs along the shallow part in northeastern and part of the channel between Misool Islands and the mainland of Papua.CONCLUSION: The interaction of barotropic tides, geomorphology, and coral reef triggers the unstratified water mass. Strong currents and turbulence on the northeast side produce homogeneous waters. The water mass in Misool waters is originated from the local dynamic.